1998
DOI: 10.1021/ac980481t
|View full text |Cite
|
Sign up to set email alerts
|

Determination of a Wide Range of Volatile Organic Compounds in Ambient Air Using Multisorbent Adsorption/Thermal Desorption and Gas Chromatography/Mass Spectrometry

Abstract: Adsorption/thermal desorption with multisorbent airsampling cartridges was developed for the determination of 87 method analytes including halogenated alkanes, halogenated alkenes, ethers, alcohols, nitriles, esters, ketones, aromatics, a disulfide, and a furan. The volatilities of the compounds ranged from that of dichlorofluoromethane (CFC12) to that of 1,2,3-trichlorobenzene. The eight most volatile compounds were determined using a 1.5-L air sample and a sample cartridge containing 50 mg of Carbotrap B and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 31 publications
2
84
0
Order By: Relevance
“…Stoichiometric model (33) showed that the calculated vapor pressures ranged from 0.122 (PFDoI) to 20.4 Torr (PFHxI) for the FIAs and 0.095 (PFDoHI) to 2.9 Torr (PFOHI) for the FTIs, which were almost the same as or even higher than the calculated values for FTOHs (0.008 Torr (10:2 FTOH) to 9.94 Torr (4:2 FTOH)) and measured results (1.08 Torr (10:2 FTOH) to 7.44 Torr (4:2 FTOH)) (29). It is widely accepted that chemicals with vapor pressures above 0.1 Torr are usually classified as volatile organic compounds (VOCs) (34) and consequently most of the PFIs can also be considered as neutral volatile fluorinated substances, which would mostly be evaporated from soil or directly emitted into the atmosphere under ambient conditions. However, heavier homologues of the FIAs and FTIs have relatively higher predicted octanol-air partition coefficient (Log K oa , e.g., 4.70 for PFDoHI and 3.23 for PFHxHI) and coefficient of fraction sorbed to atmospheric particulates (Log phi, e.g., -4.80 for PFDoHI and -6.90 for PFHxHI) (33).…”
Section: Resultssupporting
confidence: 54%
“…Stoichiometric model (33) showed that the calculated vapor pressures ranged from 0.122 (PFDoI) to 20.4 Torr (PFHxI) for the FIAs and 0.095 (PFDoHI) to 2.9 Torr (PFOHI) for the FTIs, which were almost the same as or even higher than the calculated values for FTOHs (0.008 Torr (10:2 FTOH) to 9.94 Torr (4:2 FTOH)) and measured results (1.08 Torr (10:2 FTOH) to 7.44 Torr (4:2 FTOH)) (29). It is widely accepted that chemicals with vapor pressures above 0.1 Torr are usually classified as volatile organic compounds (VOCs) (34) and consequently most of the PFIs can also be considered as neutral volatile fluorinated substances, which would mostly be evaporated from soil or directly emitted into the atmosphere under ambient conditions. However, heavier homologues of the FIAs and FTIs have relatively higher predicted octanol-air partition coefficient (Log K oa , e.g., 4.70 for PFDoHI and 3.23 for PFHxHI) and coefficient of fraction sorbed to atmospheric particulates (Log phi, e.g., -4.80 for PFDoHI and -6.90 for PFHxHI) (33).…”
Section: Resultssupporting
confidence: 54%
“…The QA/QC utilized was similar to that previous reported with little modification [27]. In brief, lot blanks, trip blanks, field blanks, travel spikes, laboratory blanks, and laboratory check standards were conducted.…”
Section: Methods Validation and Qa/qcmentioning
confidence: 99%
“…Moreover, many important perfluorinated iodine alkanes and telomer homologues were not included in the mentioned work, and thus a robust analytical method is still unavailable for this purpose. Adsorption/thermal desorption method is generally recognized and widely used as an effective technique for the analysis of a wide range of hazardous air pollutants [26][27][28][29][30] that are classified as volatile organic compounds (VOCs) and usually have vapor pressures above 0.1 Torr [27]. Compared with typical solvent-based extraction and injection scenarios, thermal desorption method requires less pretreatment procedures, reduces mass loss before quantification and enhances detection sensitivity by whole sample injection into the analytical instrument.…”
Section: Introductionmentioning
confidence: 99%
“…Sampling of duplicate samples was performed simultaneously onto two pairs of solid sorbents, connected in parallel to the air pumps. The precision of the sampling method was designated as relative standard deviation (%RSD) for each pair of duplicate samples, and was considered acceptable where RSD was lower than 20% (Pankow et al, 1998;EPA, 1999). The concentrations of target compounds in field blank samples were lower than 5% of the target compounds in real samples.…”
Section: Quality Controlmentioning
confidence: 99%